A New Indicator for the Simultaneous Complexometric Determination of Chromium(III) from Binary and Ternary Metal Ion Mixtures Using Kinetic Masking - Kumar Yadav, Vinod; Upadhyay, Rekha; Sharma, Kishore; Goswami, A.K.; Purohit, D.N. (Asian Journal of Chemistry, 2010)
A new indicator 3-hydroxy-3-phenyl-1-p-forrnylphenyltriazene was developed for the simultaneous complexometric determination of Cr(III) from binary and ternary metal ion mixtures by kinetic masking. The method is simple and efficient for the complexometric determination of trace amount of Cr(III).